Phenocryst Zonation in Porphyry-Related Rocks of the Baguio District, Philippines: Evidence for Magmatic and Metallogenic Processes. (14th May 2018) - Cao, MingJian; Evans, Noreen J; Hollings, Pete; Cooke, David R; McInnes, Brent I A; Qin, KeZhang; Li, GuangMing
ABSTRACT: Mantle-derived mafic magmas may be the source of ore-forming metals in large Cu porphyry systems, but evidence of primary petrogenetic and metallogenetic processes can be masked by hydrothermal alteration. The Baguio district of Northern Luzon, Philippines is a world-class mineral province containing approximately 40 Moz of gold and 5 Mt of copper, distributed across many porphyry Cu and epithermal Au deposit systems which are spatially related to Pliocene pre-ore Liw-Liw Creek (LCC) basaltic dikes (3·59–4·73 Ma) and a syn-ore plagioclase–hornblende diorite porphyry (2·81–2·98 Ma). A range of phenocryst phases (plagioclase, amphibole and clinopyroxene) are well preserved in both the basaltic dike suite and diorite porphyry suite, and provide an excellent natural laboratory to investigate magmatic processes and the relationship between metallogenesis and mafic magma. Widespread normally zoned clinopyroxene and amphibole grains in the basaltic dike suite show sharp decreases in Mg#, but increasing Mn, Sr, Cu, Y, Zr and REE from core to rim. Mixing of evolved felsic magma into the mafic magma is the most likely cause of these trends as fractional crystallization would typically result in gradual variations. In the diorite porphyry suite, reversely zoned amphibole is characterised by sharp increases in Mg#, Cu and Ni, but decreasing Mn, while oscillatory zoned plagioclase with distinct regions of patchy zonation shows repeated variations of An, Mg, Fe and Sr from core to rim. These signatures indicate the addition of basaltic magma to the diorite porphyry magma. The modeled Mg# of the melts (estimated assuming mineral-melt equilibrium) is also consistent with magma mixing. For example, the high Mg# of 66–72 and low Mg# of 38–44 estimated from the LLC clinopyroxene cores and rims, respectively, support the presence of basaltic magma, mixed with evolved felsic magma. All normally zoned clinopyroxene and amphibole in the basaltic dike suite and reversely zoned amphibole in the diorite porphyry suite show consistent increases in Cu from core to rim, suggesting relative enrichment of Cu in both types of injected magma. The pre-ore basaltic and ore-forming dioritic hybrid melts are estimated to have contained 45–96 ppm and 319–351 ppm Cu, respectively, based on Cu partition coefficients and zone area percentage. The Cu content of the basaltic hybrid melt is typical of arc magmas (Cu 50–100 ppm), whereas the Cu in the dioritic melt was 3–6 times higher than typical arcs magma. Both the clinopyroxene-melt thermobarometer and Al-in-hornblende geobarometer indicate similar crystallization pressures for both suites (8·6∼8·8, 4·4∼4·7, 2·1∼2·8 kbar), suggesting that both pre-ore basaltic and syn-ore dioritic suites formed in different magma chambers at similar depths. The addition of Cu enriched mafic magma may contribute ore-forming elements to the mineralising magmas and significantly increase the mineralization potential of coeval felsic rocks. Studies of phenocrysts have the potential to elucidate the role of magmatic process in the formation of porphyry systems and allow for the recognization of the key characteristics of fertile magmatic systems.